2001
DOI: 10.1002/1096-911x(20010101)36:1<160::aid-mpo1039>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of untreated patients with neuroblastoma detected by mass screening: A ?wait and see? pilot study

Abstract: At least 60% of neuroblastoma cases who entered our observation program regressed spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 5 publications
1
31
0
5
Order By: Relevance
“…These findings indicate that MS has detected tumors that otherwise may have regressed spontaneously without recognition [4,5]. Therefore, we started an observation program in the limited cases to avoid overtreatment and to estimate how frequently regression occurs (Wait and See pilot study) in June 1994 [6]. Our preliminary results have shown that at least 60% of NB cases who entered our observation program regressed spontaneously [6].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…These findings indicate that MS has detected tumors that otherwise may have regressed spontaneously without recognition [4,5]. Therefore, we started an observation program in the limited cases to avoid overtreatment and to estimate how frequently regression occurs (Wait and See pilot study) in June 1994 [6]. Our preliminary results have shown that at least 60% of NB cases who entered our observation program regressed spontaneously [6].…”
mentioning
confidence: 87%
“…Therefore, we started an observation program in the limited cases to avoid overtreatment and to estimate how frequently regression occurs (Wait and See pilot study) in June 1994 [6]. Our preliminary results have shown that at least 60% of NB cases who entered our observation program regressed spontaneously [6]. In this study, we analyzed the profile of NB resected after observation to elucidate the nature of NB detected by MS.…”
mentioning
confidence: 99%
“…Although quite intensive chemotherapy is generally recommended for aggressive or advance staged neuroblastoma [13], intensive chemotherapy is occasionally not effective for differentiated neuroblastoma, which is often observed in localized neuroblastomas. As most localized neuroblastomas have a favorable prognosis [1][2][3][5][6][7], treatment complications should be minimized. Therefore, the risks of neoadjuvant chemotherapy should be compared to surgical risks in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials to minimize treatment complications are currently ongoing worldwide. Preoperative chemotherapy or even the waitand-see observation strategy have been adapted for particular cases in some clinical trials [2,3,[5][6][7]. In these situations, the international neuroblastoma staging system (INSS) is unsuitable, as this system is a postoperative staging system.…”
Section: Introductionmentioning
confidence: 99%
“…26 With regard to the good survival and spontaneous regression found in some MS-detected NB, 27 a "wait and see" discipline is employed to avoid treatment-related complications, especially those of surgery. 28 This principle is also applied to cases incidentally detected by routine ultrasonography, with a similar favorable result. 1 However, the incidentally detected cases lack an accurate diagnosis due to lack of histological examinations.…”
Section: "Wait and See" Principlementioning
confidence: 99%